A distant OB association around RAFGL 5475 - Comerón, Fernando; Pasquali, Anna (Astronomy and astrophysics, 2019)
Context: Observations of the galactic disk at mid-infrared and longer wavelengths reveal a wealth of structures indicating the existence of complexes of recent massive star formation. However, little or nothing is known about the stellar component of those complexes. Aims: We have carried out observations aiming at the identification of early-type stars in the direction of the bright infrared source RAFGL 5475, around which several interstellar medium structures usually associated with the presence of massive stars have been identified. Our observations have the potential of revealing the suspected but thus far unknown stellar component of the region around RAFGL 5475. Methods: We have carried out near-infrared imaging observations (JHKs bands) designed to reveal the presence of early-type stars based on their positions in color–color and color–magnitude diagrams centered on the location of RAFGL 5475. We took into account the possibility that candidates found might belong to a foreground population physically related either to M 16 or M 17, two giant HII regions lying midway between the Sun and RAFGL 5475. Results: The near-infrared color–color diagram shows clear evidence for the presence of a moderately obscured population of early-type stars in the region imaged. By studying the distribution of extinction in their direction and basic characteristics of the interstellar medium we show that these new early-type stars are most likely associated with RAFGL 5475. Conclusions: By investigating the possible existence of massive early-type stars in the direction of RAFGL 5475 we have discovered the existence of a new OB association. A very preliminary assessment of its contents suggests the presence of several O-type stars, some of them likely to be associated with structures in the interstellar medium. The new association is located at 4 kpc from the Sun in the Scutum-Centaurus arm.
Gesehen am 22.02.2019